The female athlete traid - What it is and why it is important in primary care - Inman, K. L.; Hansen, K. A. (South Dakota Medicine, 2021)
The female athlete triad (FAT) is a disorder involving greater energy expenditure than energy consumption leading to 1) low energy availability (EA) with or without disordered eating 2) menstrual irregularities or amenorrhea and 3) low bone mineral density. Consequences of FAT include osteoporosis, stress fractures, increased cardiovascular risk, infertility, and negative psychological effects. The key risk factor for FAT is inadequate caloric intake when compared to the amount and intensity of exercise. All female athletes should be screened at least annually at pre-participation physicals or with signs of disordered eating, weight loss, abnormal growth or development, menstrual dysfunction, recent injuries, decreased athletic performance, or mood changes. Presence of one of the components of the triad necessitates further investigation. Treatment involves a multidisciplinary approach with increased energy intake and decreased exercise intensity being the primary goal of treatment. Understanding FAT is important for preventative medicine, as some consequences, such as infertility and loss of bone mineral density may not be reversible.